Curculiónidos de Importancia Forestal en México - Salas Araiza, Manuel Darío (Acta Universitaria, 2000)
Important forest weevils of the Mexican Republic were listed, taking as a base various of the principal insect collections of Mexico, the certificates of entry of the Colección Leopoldo Tinoco Corona of the ICA-UG (Instituto de Ciencias Agrícolas de la Universidad de Guanajuato), and reports in the literature. Cited are 33 genera and 54 species of weevils, standing out, for the number of species and ther wide distribution, the genus Pissodes with six species, and for the number forestal hosts on which they feed, Conotrachelus neomexicanus, with 10 pine species. In oak trees the larva of Curculio occidentalis and Curculio spp. damage almost 50% of the acorns. InProsopis and Acacia trees the genera Sibinia and Pantomorus predominate.
Keywords: Array; Array; Array